Developing common learning: the New Generation Project undergraduate curriculum model. - O'Halloran C; Hean S; Humphris D; Macleod-Clark J (Journal of Interprofessional Care, 2006)
This paper describes the curriculum model developed for an ambitious interprofessional education programme for health and social care professions implemented in two universities in the south of England (the New Generation Project). An outline of how the New Generation Project has interpreted the meaning of interprofessional learning is presented first. This is followed by an outline of the structure of the programme, describing both learning in common and interprofessional learning components. The pedagogies underpinning this curriculum initiative are presented and an integrated pedagogical model, facilitated collaborative interprofessional learning, is proposed. The New Generation Project curriculum is then discussed as an extension of an established typology of interprofessional education.